The influence of interest rates on its alternatives in the United Kingdom Islamic home financing - Salihu, Jamilu A (2018)
Islamic banking and finance has gained phenomenal significance since the first Islamic financial institution was established around five decades ago. However, the supposedly interest-free banking is yet to prove itself as being entirely free from the interest rate. This study focused on the rental price, house price and rental rate as possible alternatives to the interest rate benchmarking in Islamic home financing. Therefore, the objectives of the study were to investigate the long-run and the short-run as well as the causal relationship between the macroeconomic variables and each of the three dependent variables. By using the United Kingdom quarterly data for the period 2000-2016, the study employed the Autoregressive Distributed Lags (ARDL) method, Granger causality, and the Vector Error Correction Model (VECM) multivariate causality to achieve these objectives. The final results show that rental rate is free from the influence of interest rates in both the long-run and the short-run. The results further recommend rental rate as the best alternative to interest in Islamic home financing. Therefore, the outcome of the result establishes that relying on the interest rates destabilizes the alternatives to the interest rate. The findings further suggest that the market forces should determine the rental and house prices as well as the rental rate in Islamic home financing instead of relying on the interest rate. By employing these alternatives, home financing can be linked to the demand and supply of the housing market and thus is fairer to the customers as they are based on the physical attributes of the property. For the financial institutions, credit risk is mitigated as the property can be leased out based on the market value and at the same time becomes more sustainable for financing their clients.